PERANAN KOMUNIKASI ANTARPRIBADI GURU WALI DAN MURID DI SMK TJOKROAMINOTO KELURAHAN TERNATE BARU - Hatibie, Adrian (ACTA DIURNA KOMUNIKASI, 2015)
Role of Interpersonal communication Guardian and Student Teachers in Village Ternate New Vocational Tjokroaminoto. Interpersonal communication homeroom teacher and pupils in vocational Tjokroaminoto Village New Ternate. Introduction: Advances school is supported from school students regarding their knowledge, discipline, also value their politeness towards their teachers at school. Students' motivation is also highly supported by how the systems work of teachers in schools of their proximity to the teachers mereka.Dari research results through observation that not all schools have teachers who can motivate its students because of a lack of interpersonal communication is done by the teacher and his guardian. "interpersonal communication is a factor supporting the achievement of the goals of education in the learning process". Interpersonal communication is the process of delivery and acceptance of the sender and the recipient pesanantara baik.secara directly or indirectly. Said direct communication if the parties involved in the communication can share information without going through indirect communication media.Sedangkan characterized by the use of certain media. Methods: This study used qualitative research methods and the use of symbolic interaction theory. Results: The results of this study demonstrate the role of interpersonal communication homeroom teacher and pupil goes well those that do not go well. Suggestion: It is expected that interpersonal communication and his homeroom teacher bias more intensively implemented. So there is no saturation that occurs between teachers with his guardian in learning activities and character building of students. Keywords: Interpersonal Communication.